Kehidupan Sosial Ekonomi Pedagang Sagu di Desa Komba Selatan, Kecamatan Larompong, Kabupaten Luwu - Mia, Besse (UNIVERSITAS NEGERI MAKASSAR, 2018)
This research aims to: 1) Obtain information about social life of sago traders in South Komba Village, Larompong Sub-district, Luwu Regency, 2) Obtain information about economic life of sago traders in South Komba Village, Larompong Sub-district, Luwu Regency. Population 33 people. Samples taken from the entire population of 33 people. Sample determination of saturated sampling method. Descriptive. That data were obtained by using questionnaire and descriptive analysis. The results show: social life of sago traders is dominated by immigrants from Bugis area 19 out of 33 people, education level of most of elementary school graduate is 48,5% and married status. In terms of economic life the largest income they earn every day is in the range of Rp.50.000 - 100.000 per day that is as much as 60.6% and the largest expenditure ranges from Rp.500.000 - 1,000,000 as much as 48,5%. Revenue earned is able to meet daily needs. The reason they choose to sell sago is 1. not require high education, 2. No need big capital, and 3. To supplement income. The socio-economic life of sago traders in South Komba Village is quite adequate although it has to do other work, but in terms of opinion it is mostly enough to meet the needs, in terms of residence mostly occupies a permanent house of stone and half-stone house.